Studi Fenomenologi Tokoh Agama Islam dan Kristen di Kampung Toleransi Gang Luna - Dimas Muhammad Zidan Abdullah; Parihat Kamil (UPT Publikasi Ilmiah Unisba, 2024)
Abstract. Kampung Toleransi in Gang Luna, Bandung, serves as a tangible example of efforts to maintain diversity. This community reflects harmony among residents of various ethnicities, races, and religions. This study aims to explore the portrait of interfaith harmony, the experiences of Islamic and Christian religious leaders, and their interpretation of religious harmony. Using a phenomenological approach, the findings highlight three main points. First, interfaith harmony in Gang Luna has existed peacefully and harmoniously even before it was officially designated as a Kampung Toleransi. Residents have established a foundation of harmony within a multi-ethnic and multi-religious society. Second, the experiences of religious leaders reveal mutual respect, understanding, and efforts to educate their communities to live peacefully. Third, the meaning of religious harmony, according to these leaders, includes the freedom to practice beliefs without judgment. In terms of social interactions (muamalah), strong cooperation is evident through mutual assistance, community service, and joint celebrations such as independence commemorations. Abstrak. Kampung Toleransi di Gang Luna, Kota Bandung, menjadi contoh nyata upaya menjaga keberagaman. Kampung ini mencerminkan kerukunan antarwarga dari berbagai suku, ras, dan agama. Penelitian ini bertujuan untuk mengungkap potret kerukunan umat beragama, pengalaman tokoh agama Islam dan Kristen, serta makna kerukunan menurut kedua tokoh tersebut. Dengan pendekatan fenomenologi, hasil penelitian menunjukkan tiga poin utama. Pertama, kerukunan umat beragama di Gang Luna telah berjalan damai dan harmonis bahkan sebelum diresmikan sebagai Kampung Toleransi. Warga telah membangun fondasi keharmonisan di tengah masyarakat multi etnis dan agama. Kedua, pengalaman tokoh agama menunjukkan saling menghargai, saling menghormati, dan memberikan pemahaman kepada umat untuk hidup damai. Ketiga, makna kerukunan menurut tokoh agama melibatkan kebebasan dalam aspek aqidah dan ibadah tanpa saling menghakimi. Dalam aspek muamalah, terjalin kerja sama erat melalui gotong royong, tolong menolong, kegiatan sosial, dan perayaan bersama seperti tasyakur agustusan.